2011
DOI: 10.3758/s13428-011-0073-0
|View full text |Cite
|
Sign up to set email alerts
|

Mode-of-disparities error correction of eye-tracking data

Abstract: In eye-tracking research, there is almost always a disparity between a person's actual gaze location and the location recorded by the eye tracker. Disparities that are constant over time are systematic error. In this article, we propose an error correction method that can reliably reduce systematic error and restore fixations to their true locations. We show that the method is reliable when the visual objects in the experiment are arranged in an irregular manner-for example, when they are not on a grid in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 8 publications
1
37
0
Order By: Relevance
“…Komogortsev and Khan (2008), for example, used an eyetracker with an accuracy specification of 0.5°but found that, after removing all invalid recordings, the average accuracy over participants was 1.0°. Zhang and Hornof (2011), Hansen and Ji (2009), and others have reported similar results. Furthermore, accuracy depends strongly on the particular characteristics of the individual participant (Hornof & Halverson, 2002), with head movements, astigmatism, and eyelid closure being particularly troublesome factors that can cause inaccuracies of several degrees of visual angle and can be detrimental to position-based data analysis and interaction.…”
supporting
confidence: 68%
“…Komogortsev and Khan (2008), for example, used an eyetracker with an accuracy specification of 0.5°but found that, after removing all invalid recordings, the average accuracy over participants was 1.0°. Zhang and Hornof (2011), Hansen and Ji (2009), and others have reported similar results. Furthermore, accuracy depends strongly on the particular characteristics of the individual participant (Hornof & Halverson, 2002), with head movements, astigmatism, and eyelid closure being particularly troublesome factors that can cause inaccuracies of several degrees of visual angle and can be detrimental to position-based data analysis and interaction.…”
supporting
confidence: 68%
“…The technique uses RFLs [Hornof and Halverson, 2002] and PFLs [Zhang and Hornof, 2011] to measure eye tracking error, and uses quadratic equations to characterize the change in error across the display. Example data from an eye tracking experiment demonstrate that eye tracking error that initially appears to be somewhat random can actually follow a smooth quadratic curve.…”
Section: Resultsmentioning
confidence: 99%
“…Because the number was small (0.26º in height), the participants had to look directly at the numbers to find the target. Similar to Zhang and Hornof [2011], fixations in this condition were mapped to their nearest PFLs. As mentioned earlier, the RFLs were given a larger weight than the PFLs in the robust linear regression computation.…”
Section: Validation Of the Error Correction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem is increased if the analysis has to be rerun, in case for example some objects (e.g., windows) are to be removed from the analysis or the calibration of the eye tracker had a small divergent. The online matching of dynamic AOIs also has the disadvantage of not applying any method for correcting the eye-movement data (Hornof & Halverson, 2002;Zhang & Hornof, 2011). Due to the research presented above, the authors believe that, at present, methods of replay and post correction are necessary in the field of eyemovement analysis.…”
Section: Existing Approachesmentioning
confidence: 99%